ScriptoAI: Transforming Text, Images & Speech into Seamless Digital Handwriting - Beenish Riaz; Syed Abdullah Raza; Mujahid Hussain; Zakir Ullah (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Inscriptive is an AI-powered web-based platform designed to convert typed text, PDFs, and assignments into lifelike handwritten styles. With a diverse collection of 30 to 40 handwriting styles, customization options for fonts and page colors, and advanced text processing capabilities, it serves as a comprehensive solution for students, educators, and professionals. A key feature of inscriptive is its AI-driven Optical Character Recognition (OCR) technology, which enables users to extract text from images, scanned documents, and handwritten notes with high accuracy. By leveraging machine learning algorithms, the OCR system enhances image quality, detects textual patterns, and converts them into an editable digital format, allowing seamless content modification and handwriting transformation. Additionally, Inscriptify integrates AI-based voice-to-text conversion, allowing users to dictate content that is automatically transcribed into digital text. This feature is particularly useful for students who prefer speaking their notes instead of typing, professionals needing hands-free document creation, and individuals requiring speech-to-text assistance for accessibility. Through AI-powered processing, rigorous research, iterative development, and continuous optimization, inscriptive aims to provide a user-friendly, scalable, and efficient solution that streamlines creative workflows